Counteracting social vulnerability and marginality through education - Marcella Milana (University of Bologna, 2021)
This contribution contextualizes the relationship between fragility and education in the light of people's changing conditions and perspectives, and their impact on educational processes, focusing in particular on the consequences of the outbreak of the Covid-19 pandemic. By doing so, it introduces this focus, illustrates its coherence, and explains the basic methodological choice, namely the adoption of the Systematic Review, to explore different aspects of the relationship between fragility and education.